1996
DOI: 10.3109/13547509609079346
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker protein expression in primary cultures of salmon (Salmo salar L.) hepatocytes exposed to environmental pollutants

Abstract: Primary cultures of salmon (Salmo salar L.) hepatocytes were analysed using (35)s-methionine/cysteine incorporation and SDS-PAGE gel electrophoresis (1 and 2-D) and Western blotting after treatment with representative environmental pollutants (benzo(a)pyrene (BaP), 2,3,3', 4,4'-pentachlorobiphenyl (PCB-105)1 arsenite (AsO2-) and cadmium (Cd)). The results demonstrated striking similarities in changes in protein expression after treatment with the different pollutants. Hsp70 (Hsp72/73) proteins were induced aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Indeed, it has been shown that several forms of environmental stressors can induce the hsp response in fish. For example, increased levels of various hsps have been measured in tissues of fish exposed to industrial effluents , polycyclic aromatic hydrocarbons , several metals such as copper, zinc and mercury (Sanders et al, 1995;Williams et al, 1996: Duffy et al, 1999, pesticides (Hassanein et al, 1999) and arsenite (Grosvik and Goksoyr, 1996). These studies and others revealed that the use of hsp as an indicator of stressed states in fish is a very complex issue.…”
Section: Heat Shock Proteins As Indicators Of Stressmentioning
confidence: 99%
“…Indeed, it has been shown that several forms of environmental stressors can induce the hsp response in fish. For example, increased levels of various hsps have been measured in tissues of fish exposed to industrial effluents , polycyclic aromatic hydrocarbons , several metals such as copper, zinc and mercury (Sanders et al, 1995;Williams et al, 1996: Duffy et al, 1999, pesticides (Hassanein et al, 1999) and arsenite (Grosvik and Goksoyr, 1996). These studies and others revealed that the use of hsp as an indicator of stressed states in fish is a very complex issue.…”
Section: Heat Shock Proteins As Indicators Of Stressmentioning
confidence: 99%
“…It has been shown that several forms of environmental stressors may induce the Hsp response in fish. For example, increased levels of various Hsps have been measured in tissues of fish exposed to industrial effluents, polycyclic aromatic hydrocarbons , several metals such as copper, zinc and mercury (Sanders, 1993;Williams et al, 1996), pesticides (Hassanein et al, 1999) and arsenite (Grosvik and Goksoy, 1996). These studies and others revealed the use of Hsp as an indicator of stressed states in fish is a complex issue.…”
Section: Functionmentioning
confidence: 99%
“…HSP induction in response to hyperammonemic conditions has been documented in carp (Hernandez et al 1999). Enhanced levels of different HSPs have also been demonstrated in tissues of fish exposed to polycyclic aromatic hydrocarbons ), metals such as copper, zinc, and mercury (Duffy et al 1999;Williams et al 1996), pesticides (Hassanein et al 1999), and arsenite (Grosvik and Goksoyr 1996). Cara et al (2005) reported the impact of fooddeprivation, reduced oxygen levels, and heat shock on the expression of HSP70 and HSP90 in the early life stages of the gilthead sea bream (Sparus aurata), a warmwater aquaculture species.…”
Section: Role Of Stress Proteins In Fishmentioning
confidence: 99%